Ophthalmic complications of Lemierre syndrome. Issue 1 (8th April 2021) - Kreuzpointner, Robert; Valerio, Luca; Corsi, Gabriele; Zane, Federica; Sacco, Clara; Holm, Karin; Righini, Christian; Pecci, Alessandro; Zweifel, Sandrine; Barco, Stefano
Abstract: Purpose: Lemierre syndrome is a life‐threatening condition characterized by head/neck bacterial infection, local suppurative thrombophlebitis and septic embolic complications in a range of sites of distant organs. No prior study focused on the course and characteristics of ophthalmic complications of Lemierre syndrome. Methods: We analysed data of 27 patients with ophthalmic complications from a large cohort of 712 cases with Lemierre syndrome reported globally between 2000 and 2017. We focused on initial manifestations, early (in‐hospital) course and long‐term ophthalmic deficits at the time of hospital discharge or during postdischarge follow‐up. The study protocol was registered in the International Prospective Register of Systematic Reviews PROSPERO (CRD42016052572). Results: Nine (33%) patients were women; the median age was 20 (Q1–Q3: 15–33) years. Fusobacterium spp . was involved in 56% of cases. The most prevalent initial manifestations were decreased vision (35%) and periocular oedema (38%), followed by impaired eye movements/nerve palsy (28%) and proptosis (28%). Venous involvement, notably cerebral vein thrombosis (70%) and ophthalmic vein thrombosis (55%), explained the symptomatology in most cases. Septic embolism (7%), orbital abscesses (2%) and carotid stenosis (14%) were also present. Ophthalmic sequelae were reported in 9 (33%) patients, often consisting of blindness or reduced visual acuity, and nerve paralysis/paresis. Conclusion: Ophthalmic complications represent a severe manifestation of Lemierre syndrome, often reflecting an underlying cerebral vein thrombosis. Visual acuity loss and long‐term severe complications are frequent. We call for an interdisciplinary approach to the management of patients with Lemierre syndrome and the routine involvement of ophthalmologists.